Adros: investigação sobre uma ação plástica: desenho - Getulio Jose Moreira (2006)
This text is resulted of a research beyond ones plastic action. Throughimplications of the elements Theoricals/Praticals, couple being considered in therange properly human, as such: thinking, willing, moving, and its own suppositions,by means of them being able to realize, in the specific sense of this investigation: onesimple draw.